2017
DOI: 10.1016/j.csda.2016.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Optimal designs for comparing regression models with correlated observations

Abstract: We consider the problem of efficient statistical inference for comparing two regression curves estimated from two samples of dependent measurements. Based on a representation of the best pair of linear unbiased estimators in continuous time models as a stochastic integral, an efficient pair of linear unbiased estimators with corresponding optimal designs for finite sample size is constructed. This pair minimises the width of the confidence band for the difference between the estimated curves. We thus extend re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Finally, optimal designs for the comparison of curves have been developed, which minimizes the maximum width of the confidence band for the difference between two regression functions. In particular, it was demonstrated that the application of optimal designs instead of commonly used designs yields a reduction of the width of the confidence band by more than 50% [ 86 , 87 ].…”
Section: Extrapolationmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, optimal designs for the comparison of curves have been developed, which minimizes the maximum width of the confidence band for the difference between two regression functions. In particular, it was demonstrated that the application of optimal designs instead of commonly used designs yields a reduction of the width of the confidence band by more than 50% [ 86 , 87 ].…”
Section: Extrapolationmentioning
confidence: 99%
“…In summary, we developed a new optimized design and analysis strategy for comparing dose-response profiles to extrapolate clinical trial results from a larger to a smaller population. The comparison of dose response curves should be done by the bootstrap approach [ 47 , 87 ]. If the aim of the study is the extrapolation of efficacy and safety information, we recommend considering and comparing the MEDs of two given populations [ 84 ].…”
Section: Extrapolationmentioning
confidence: 99%
See 1 more Smart Citation
“…Another body of work investigated optimal designs under continuous time regression models with correlated errors (Dette et al 2016, Dette, Konstantinou & Zhigljavsky 2017, Dette, Schorning & Konstantinou 2017, Dette et al 2018), including continuous time versions of model (1)- (3) Unfortunately, in practice, V is never known, which makes it impossible to use the GLSE with W = V , or the optimal designs for the GLSE with W = V .…”
Section: Introductionmentioning
confidence: 99%
“…The optimal design problem focusing on the width of the simultaneous confidence bands can be formalized in a different way. When comparing two estimated regression curves, Dette and Schorning (2016) and Dette, et al (2017) proposed to minimize the L por L ∞ -norm of the variance function of the estimator of the difference between the two curves. They demonstrated that their proposal reduces the width substantially compared with the pair of optimized designs for individual regression models.…”
Section: Introductionmentioning
confidence: 99%